1993
DOI: 10.1038/bjc.1993.167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by a new bisphosphonate (YM175) of bone resorption induced by the MBT-2 tumour of mice

Abstract: Summary A new bisphosphonate, disodium dihydrogen (cycloheptylamino) methylene bisphosphonate monohydrate (YM175), was compared with 3-amino-1-hydroxypropylidene-1, 1-bisphosphonate (AHPrBP) and l-hydroxyethylidene-1,1-bisphosphonate (HEBP) in terms of its effect on tumour induced osteolysis using a bladder tumour in mice (MBT-2). The method consisted of inoculating tumour cells subcutaneously (SC) (Fleisch et al., 1969;Fleisch & Felix, 1979;Fleisch, 1983). Inhibition of tumour induced osteolysis by bisphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It has been clearly shown that several different bisphosphonates can reduce tumor-induced osteolytic bone disease in animal models of a variety of cancers that metastasize to bone, including breast (8,10,32,33), bladder (34,35), and prostate cancer (16, 36 -38) as well as multiple myeloma (11,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly shown that several different bisphosphonates can reduce tumor-induced osteolytic bone disease in animal models of a variety of cancers that metastasize to bone, including breast (8,10,32,33), bladder (34,35), and prostate cancer (16, 36 -38) as well as multiple myeloma (11,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies during the past two decades have clearly demonstrated that a variety of bisphosphonates can reduce tumor-induced osteolysis in animal models of breast, [43][44][45][46][47][48][49][50][51][52] prostate, 33,[53][54][55][56][57][58][59][60] and bladder cancer, [61][62][63][64] as well as multiple myeloma. 42,[65][66][67][68][69] By inhibiting osteoclast-mediated bone resorption, bisphosphonates decrease the release of tumor-promoting growth factors from bone and delay the further progression of bone metastases.…”
Section: Inhibition Of Bone Metastases In Vivomentioning
confidence: 99%
“…Bisphosphonates inhibit osteoclastic bone resorption with little or no effect on the renal reabsorption of Ca [8,10,22]. The substantial effect of bisphosphonate in restoring normocalcemia indicated that the HHM of the patient was caused mainly by increased osteoclastic activity.…”
Section: Discussionmentioning
confidence: 91%